Children's exposure to sustainability practices during the transition from preschool into school and their learning and socioemotional development. Issue 2 (3rd April 2017) - Benner, Aprile D.; Thornton, Anna; Crosnoe, Robert
ABSTRACT: Evidence that the learning gains of preschool fade as children transition into elementary school has led to increased efforts to sustain preschool advantages during this key transitional period. This study explores whether the observed benefits of sustainability practices for a range of child outcomes are explained and/or moderated by family and school mechanisms selecting children into experiencing these practices. Analyses of the Early Childhood Longitudinal Study-Birth Cohort revealed that both family and school factors predicted children's exposure to several PK-3 sustainability practices. PK-3 sustainability practices were associated with reading (but not math) gains and better interpersonal skills (but not fewer externalizing behaviors) following the transition into kindergarten. These links were not conditioned by the selection mechanisms. The findings highlight who is more likely to seek out (at the family level) or offer (at the school level) sustainability practices and how relevant they are to fighting preschool fadeout.